Komunikasi Internal dan Iklim Organisasi sebagai Determinan Kepuasan Kerja Pegawai di Pusjar SKMP LAN Makassar - Febrianti Rara Topadang; Nurman Nurman; Burhanuddin Burhanuddin; Agung Widhi Kurniawan; Rezky Amalia Hamka (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine the effect of internal communication and organizational climate on employee job satisfaction at the Center for Learning and Government Management Policy Strategy, National Institute of Public Administration (Pusjar SKMP LAN) Makassar. The research employed a quantitative approach with an explanatory design. The population consisted of all 73 employees of Pusjar SKMP LAN Makassar, and a saturated sampling technique was applied. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression after meeting validity, reliability, and classical assumption requirements. The results indicate that internal communication and organizational climate simultaneously have a positive and significant effect on employee job satisfaction. Partially, internal communication shows a more dominant influence compared to organizational climate. These findings suggest that information clarity, effective communication channels, timely information delivery, and open feedback mechanisms play a crucial role in enhancing job satisfaction. Furthermore, a supportive organizational climate characterized by leadership support and harmonious working relationships strengthens employee comfort and engagement. This study contributes theoretically to the development of human resource management literature in the public sector and provides practical implications for improving internal communication management and organizational climate within government institutions.